The Principle of Justice in the Minimum Capital Policy for Foreign Direct Investment (A Study of Fraudulent Foreign Direct Investment Companies in Bali) - Khairunnisa Wiladi Putri; Iwan Erar Joesoef (Law Development Journal, 2025)
Foreign Direct Investment (FDI) holds a strategic role in the Indonesian economy, particularly in fostering industrial development and creating employment opportunities. However, the minimum capital policy stipulated in Regulation No. 4 of 2021 of the Indonesian Investment Coordinating Board (BKPM) poses significant challenges for its implementation. This study aims to analyze the effectiveness of the policy, focusing on the case of fraudulent foreign direct investment companies in Bali, and to compare Indonesia’s minimum capital policy for foreign direct investment with similar policies in Vietnam. Using a normative legal approach with statutory, comparative, and case study methods, this study found that the uniform minimum capital requirement actually constrains investment potential in certain sectors, such as tourism, which should require more flexible capital provisions. Another finding indicates that weak supervision and law enforcement create loopholes for administrative manipulation, such as fictitious capital deposits and the use of nominees, ultimately undermining the integrity of the investment system and creating injustice for law-abiding business actors. Based on this analysis, this study recommends adjusting the minimum capital policy to be more responsive to each sector's characteristics, strengthening transparency in supervision, and implementing stricter law enforcement to prevent abuses that harm the national economy. The results of this study are expected to contribute to improving Indonesia’s investment policy, creating a fairer investment climate, and supporting sustainable and inclusive economic development.